Effect of functional groups on microporous polymer based resistance switching memory devices. Issue 47 (11th May 2020) - Song, Yaru; Liu, Jie; Li, Wanhui; Liu, Lei; Yang, Ling; Lei, Shengbin; Hu, Wenping
Abstract : Here, two large-area microporous polymer (MP) films with different substituents were synthesized at the solution/air interface. Abstract : Here, two large-area microporous polymer (MP) films with different substituents were synthesized at the solution/air interface. The on/off ratios of the MP-based memristors differ by an order of magnitude and the turn-on voltages differ by about 0.2 V, which is mainly attributed to the difference in band gap and pore environment of the materials.